2013
DOI: 10.1007/s13593-013-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon selection by root system size increases barley yield

Abstract: International audienceMost agronomy practices such as fertilization, irrigation, and soil treatment involve plant root interactions. However, the role of plant roots is rarely assessed during agricultural experiments due to the lack of suitable methods. Plant varieties with a larger root system use soil water and nutrients in dry environments more effectively than varieties with a smaller root system. Such large root varieties can be developed by breeding. Therefore, we evaluated the effects of selection for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 27 publications
3
55
0
3
Order By: Relevance
“…Also Rychnovská et al (1985) highlights the relation between drought, root formation dynamics, and consequently reduction of the leaf area, photosynthesis and production. Increased production of alfalfa root with a larger root capacity (electrical capacitance) is stated by Chloupek et al (1999);Svačina et al (2014) confirms this in selected material of spring barley. Increasing the electrical capacitance by + 3.9% led to a production response almost two times higher (+ 8.1%).…”
Section: Introductionsupporting
confidence: 53%
“…Also Rychnovská et al (1985) highlights the relation between drought, root formation dynamics, and consequently reduction of the leaf area, photosynthesis and production. Increased production of alfalfa root with a larger root capacity (electrical capacitance) is stated by Chloupek et al (1999);Svačina et al (2014) confirms this in selected material of spring barley. Increasing the electrical capacitance by + 3.9% led to a production response almost two times higher (+ 8.1%).…”
Section: Introductionsupporting
confidence: 53%
“…It is important to emphasize that measurement data are comparable only among plants of the same species, grown in the same substrate at the same moisture level in the same time frame (Chloupek et al, 2010). Due to its versatile adaptability, EC measurement can be reliably applicable in various fields of basic and applied plant physiology, ecopysiological and agricultural researches, substituting at least partially the intrusive and labour intensive techniques Cao et al, 2010;Cseresnyés et al, 2012Cseresnyés et al, , 2013aSvačina et al, 2014). CONCLUSIONS 1.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences are marked by different letters; different were only combinations U3 (Prestige × Diplom) and U11 (Diplom × Saloon). Svačina et al (2013) used the identical parents and combination as in our study. Evaluation of the general combining ability showed that the use of Saloon and Diplom parents led to an increased root system size in both selection.…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%